Managed healthcare: ethical implications on the doctor-patient relationship - Masege, Dipuo (My University, 2022)
Managed health system remains a topical issue worldwide. The main concern is whether it is an ideal method for the provision of health care in an effective and efficient manner whilst at the same time curbing spiralling healthcare costs. South Africa is not spared this debate on managed health care. The main aim being to guarantee that cost-effective quality healthcare is provided to patients who are members of a medical aid scheme within the managed healthcare context (Mahlo & Muller, 2000, Pg. 37; Booyens, 2000 ) In implementing managed healthcare, there are resultant unforeseen ethical implications which may have an effect on the doctor patient relationship. In view of these ethical implications, I set forth to look at to what extent these have on the doctor patient relationship. The focus of this research report is to argue that one of untoward ethical consequences that managed health care has brought about is the impact it has on this relationship. Thus, the question being posed is, is it ethically justifiable for managed healthcare to interfere in the doctor- patient relationship? This report was purely normative, involving online library sources, academic search engines and desktop-based research to obtain the literature. Ethical arguments and counterarguments are presented in the research report regarding the ethical issues managed healthcare has on the doctor patient relationship. Ethical principles and theories were used to bolster the focus of the argument that the relationship is negatively impacted. I explored principles of autonomy(both of the doctor and the patient) , beneficence and maleficence in support of the relationship , with counter-argument in justice and redistribution of scarce resources. Therefore I concluded by arguing, that managed healthcare has adverse ethical consequences on doctor –patient relationship
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Bioethics and Health Law to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022